Program evaluation in school counseling : improving comprehensive and developmental programs - Trevisan, Michael S.; Carey, John C. (New York: Routledge, 2020)
"Program Evaluation in School Counseling is the first book on program evaluation that looks to the field and literature of program evaluation and then relates methods, procedures, and practices back to the practice of school counseling. Written by two accomplished authors who teamed up to build evaluation capacity among school and school-based counselors internationally, the book highlights their interdisciplinary work, covering many years and several continents. Based on the authors' model for teaching program evaluation and their research on school counselor competence in program evaluation, this concise, clear and practical guide supports the continuing professional development of school counselors through training, workshops and self-study. This book addresses the program evaluation knowledge, skills, and understandings that school-based counselors are expected to use in line with the CACREP 2016 Standards. The book is intended as a companion text for university courses in research methods and/or in the organization and administration of counseling services. It is also appropriate as a self-study guide to help practicing school counselors develop expertise in evaluation"--
Toward a conceptual understanding of evaluation for school counselors -- Evaluation and the school counseling program and profession -- Involving stakeholders -- Developing theories of action and logic models -- Developing school counseling program evaluation questions -- The evaluation design and methods -- Data analysis for quantitative data -- Data analysis for qualitative data -- Reporting evaluation results and using findings -- Evaluation knowledge skills and practice.
Includes bibliographical references and index.
Keywords: Educational counseling -- United States -- Evaluation; Evaluation research (Social action programs) -- United States